(3eQBI GdReGf aj JhGQjN GdGYjGfs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s
(3ChdgG (B:s
(3jHOC HGdSfI GdSGHYI hGdSJhf HYO GdeGFI s
(3BNQgG (B:s
(3jfJgi HPcQ hajGJ SfI JSY HYO GdeGFJjf(B) (3hajgG Jhai SYjO Hf hgH CHh YKeGf GdHUQi hcGfJ haGJg ai gPG GdSfI , hcGf YTQ Hfjf hYTQ HfGJ ced GdLRAGdJGSY jJdhg Ef TGA Gddg ai GdLRA GdYGTQ GdSfI GdYGTQI HYO GdeGFJjf s
(3YdjgG Jedc HGSe CHj HcQ Hf CMeO Hf GdTgjOs
(3hJde BNQ SfI (B770 (3g`s
(3gcPG cJH Ydi GdeNWhW Gfg dGHf GdLhRi eY Cf GdeYQha Gfg dSHWg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1647s
Keywords: (3GdJGQjNs